THE INFLUENCE OF SPIRITUAL, INTELECTUAL, AND EMOTIONAL INTELLIGENCE ON AUDIT QUALITY - Menne, Firman; Saleh, Muhammad Yusuf; Aziz, Muhammad Agung (Jurnal Iqtisaduna, 2019)
This study aims to investigate the influence of spiritual, intellectual and emotional intelligence on audit quality, case studies at Public Accounting Firms in Makassar City. Spiritual intelligence is intelligence possessed by each individual that is related to the human soul and morality. Intelectual Intelligence is possessed by organisms to adapt effectively to complex environments and always change and are influenced by genetic factors. Emotional Intelligence is an ability to understand feelings of self with others, motivate themselves and manage emotions themselves and others. Data are collected through questionnaires with 49 respondent as a number of public accoutant form eight Public Accounting Firms in Makassar. Methods of data analisys using the SPSS to analyze the influence of the Spiritual Intelligence, Intellectual Intelligence and Emotional Intelligence on Audit Quality, case studies in Public Accounting Firms in Makassar City. The result of this study showed that spiritual, Intellectual, and emotional intelligence partially and simultaneously had a positive and significant effect on audit quality.